Exploring the spatialities of institutional entrepreneurship in Taipei's FinTech industry. Issue 11 (2nd November 2022) - Lin, Cheng-Yi
ABSTRACT: This paper contributes to developing the spatiality of institutional entrepreneurship as an analytical framework and using the framework to explore the case of Taipei's financial technology (FinTech) industry. It argues that FinTech start-ups leverage multiple spatialities to engage in strategic involvement with the four forms of institutional change. Meanwhile, Taipei's FinTech industry displays a dual-track institutional entrepreneurship strategy: conforming with the state–finance regime to gain legitimacy by being in the FinTech space and building the FinTech scene by developing local and translocal project networks. These dual strategic–institutional practices are central to changing existing financial service institutions, markets and regulations in a latecomer city context.